Seeking forgiveness from Holika - Mumbai Archive Project Team (Jio Institute, 2024)
Before starting any ritual, married women in the family bathe and dress in new Nauvari sarees (a nine-yard saree worn by Koli women). They then clasp their ears as a gesture of seeking forgiveness from Holika for any past transgressions.